Vocal repertoire of long-finned pilot whales (Globicephala melas) in northern Norway - Heike Vester and Sarah Hallerberg and Marc Timme and Kurt Hammerschmidt (The journal of the Acoustical Society of America, 2017)
The knowledge of the vocal repertoire of pilot whales is very limited. In this paper, the vocal repertoire of long-finned pilot whales recorded during different encounters in the Vestfjord in northern Norway between November 2006 and August 2010 are described. Sounds were analysed using two different methods: (1) an observer-based audio-visual inspection of FFT-derived spectrograms, with which, besides a general variety of clicks, buzzes, nonharmonic sounds, and whistles, 129 different distinct call types and 25 subtypes were distinguished. These call types included pulsed calls and discrete structured whistles varying from simple to highly complex structures composed of several segments and elements. In addition, ultrasonic whistles previously not described for pilot whales were found. In addition to the diversity of single calls, call sequences consisting of repetitions and combinations of specific call types were recorded and (2) a parametric approach that permitted the confirmation of the high variability in pilot whale call structures was developed. It is concluded that the pilot whale vocal repertoire is among the most complex for the mammalian species and the high structural variability, along with call repetitions and combinations, require a closer investigation to judge their importance for vocal communication.
Keywords: Speech communication; Vocalization; Bioacoustics of mammals; Acoustic parameters; Ultrasonics; Spectrograms; Animal communication; Animal sounds; Water transportation; Representation theory